PENGAMBILAN KEPUTUSAN RUMAH TANGGA DALAM MEMBELI SAUS SAMBAL BOTOL DI BANDAR LAMPUNG - Sastra Delila; Yaktiworo Indriani; Suriaty Situmorang (Lampung University, 2015)
The objective of this research were to know the effect of bottled chilli sauche atributes to decision making of buying bottled chili sauce and the influencing buying factors on bottled chilli sauce in Bandar Lampung. This research employed qualitative and quantitative survey method. The location was determined by using stage groups method. The total samples of 81 household whose housewives served as respondents were chosen by simple random sampling from the groups. This research data was collected in April - May 2014. The data was analyzed by conjoint and multiple linear regression analysis. The result of conjoint analysis showed that the most preferred attributes of bottled chili sauce were spicy, reddish orange color, bigger than 250 ml and packaging in glass bottle. Most of the respondents choose ABC and Indofood brands as their bottled chili sauce because of the quality, hot taste and good price. The factors that significantly influenced the buying of bottled chili sauce were the price, wife’s education, household income, the dummy variables of brand and advertisement. Key words: bottled chili sauce, conjoint, decision making